HOLDING RECREATIONAL SPORTS IN THE GUNDALING HILLS OF BERASTAGI AS A SOURCE OF THE SPORTS INDUSTRY - Herli E steria Br Ginting (Indonesia Sport Journal, 2022)
ABSTRACTThis study aims to find out how big the opportunity for Gundaling Hill to be used as a Sports Industry Source by holding Recreational Sports on the Hill. The method that will be used for this research is descriptive qualitative. This research is a research that has not happened at all in Karo soil. And it has not been done at all in the Karo land area, especially in the Gundaling Berastagi hill. The subjects in this study were human resources in the Gundaling hill area of Berastagi, Tanah Karo. The data collection technique in this research is using interview, observation, and documentation guidelines. The data analysis of this research is by data reduction, data presentation and verification. The guidelines that have been carried out based on interview tests are obtained that the opportunity to create a recreational sports program as a sports industry can be developed in the Gundaling Hill area. Based on the data that will be met with various questionnaires and interviews and documents obtained from support for approval as the Gundaling hill area which is used as a sports industry by opening up opportunities to create recreational sports programs will be realized.Keywords: Development, Recreational Sports, Sports Industry